PENGKODE WAVEFORM INTERPOLATION DENGAN LAJU DATA 4,15 KBPS - Fauzi, Muhammad
The need of a narrowband speech coder delivering near-toll-quality speech at rates of 4 kbps and below is increasing, motivated by the expanding varieties of applications for speech coding, such as third generation wireless networks, etc. Waveform Interpolation (WI) coder is one of candidates to fulfill the need. The primary objective of this research is to develope a WI based speech coder at rates around 4 kbps which can deliver quality better than or equivalent to that of FS1016 coder. Pitch estimator is very crucial to the performance of WI coder. Fix phase spectrum attachment at Slowly Evolving Waveform (SEW) amplitude spectrum creates distortion in pitch multiple segments of WI coder [1). In addition to the primary objective, this research also aims to increase the performance of WI coder by increasing the performance of pitch estimator, decreasing the effect of fix phase spectrum attachment and increasing the performance of analysis synthesis of pitch (sub) multiple segments. WI coder at rate 4.15 kbps has been simulated using MATLAB programming language. The WI coder performance is tested by subjective test. There are 4 test utterances, each of them was processed by the WI coder and the FS1016 coder. The resulting pairs were presented to 9 listeners resulting 36 opinions. WI coder is equivalent to FS1016 coder for 41,67% of the opinions.